ARCHITECTS OF TOXIC POLITICS IN AMERICA - Walsh, Kenneth T. ([S.l.])
1 online resource
Keywords: The Architects of Toxic Politics in America: Venom and Vitriol explains the history of poison politics in America by profiling some of the key political attack dogs who have shaped the modern landscape. Comparing and contrasting the Trump and Biden presidencies with administrations of the past, the book explains the unique character of the current toxic political moment and the forces that have created it.The book also focuses quite extensively on non-presidential architects of toxic politics: other politicians, campaign strategists, activists, and media figures (and a few key figures that have fulfilled two or more of these roles). Drawing on his long career as a journalist specializing in presidential coverage, Kenneth T. Walsh argues that due to the complex, often conflicting nature of American government, the angriest, most decisive voices can command media, voter, and legislative attention and thereby maintain and consolidate power. This results in frustration, alienation, and cynicism--and ultimately, a diminishment of voter participation that can reinforce the vicious cycle and lead to electoral disaster. For anyone interested in politics, media, and the culture of gotcha journalism, this book will also be a valuable addition to undergraduate and graduate courses on politics, the presidency, political and media ethics, campaign history and government.